Концептуальные основы государственного регулирования организационно-экономического механизма производства продукции животноводства - Ремизова, Н.Я. (Культура народов Причерноморья, 2014)
В статье рассматриваются современные концептуальные основы государственного
регулирования организационно-экономического механизма производства продукции животноводства.
Приводится когнитивная карта взаимодействия государственных интервенций и объемов
производимой продукции животноводства в сельскохозяйственных предприятиях. Определены суть,
структура, особенности и основная цель государственного воздействия на организацию
интеграционных объединений. У статті розглядаються сучасні концептуальні основи державного регулювання
організаційно-економічного механізму виробництва продукції тваринництва. Приводиться когнітивна
карта взаємодії державних інтервенцій і об'ємів продукції тваринництва в сільськогосподарських
підприємствах. Визначені суть, структура, особливості і основна мета державної дії на організацію
інтеграційних об'єднань. Modern conceptual bases of government control of organizational-economic mechanism of
production of goods of stock-raising are examined in the article. A kognitiv map over of co-operation of state
interventions and volumes of producible products of stock-raising is brought in agricultural enterprises.
Essence, structure, features and primary purpose of the state affecting organization of integration associations,
is certain.
The purpose of this paper is to study the conceptual foundations of state regulation of organizational and
economic mechanism of livestock production
The most efficient production in modern conditions have integration associations, which include processing
plants.
Determination of the intensity of the relationship was carried out with the help of expert judgments of
agriculture, heads of agricultural enterprises and teachers, graduate students
Implementation of the defined priority areas as the basis for improving the organizational-economic mechanism
of livestock production in the agricultural enterprises provide effective change, and improve the profitability and
competitiveness of the industry.
State support for agricultural livestock producers should primarily be aimed at supporting the production.
Implement sound policies pricing regulation for meat will allow farmers to plan production volumes created
integration groups.